CXC chemokine ligand 12a enhances chondrocyte proliferation and maturation during endochondral bone formation. Issue 6 (June 2015) - Kim, G.-W.; Han, M.-S.; Park, H.-R.; Lee, E.-J.; Jung, Y.-K.; Usmani, S.E.; Ulici, V.; Han, S.-W.; Beier, F.
Summary: Objective: We investigated the roles of CXC chemokine ligand 12a (CXCL12a), also known as stromal cell-derived factor-1α (SDF-1α), in endochondral bone growth, which can give us important clues to understand the role of CXCL12a in osteoarthritis (OA). Methods: Primary chondrocytes and tibial explants from embryonic 15.5 day-old mice were cultured with recombinant mouse CXCL12a. To assess the role of CXCL12a in chondrogenic differentiation, we conducted mesenchymal cell micromass culture. Results: In tibia organ cultures, CXCL12a increased total bone length in a dose-dependent manner through proportional effects on cartilage and bone. In accordance with increased length, CXCL12a increased the protein level of proliferation markers, such as cyclin D1 and proliferating cell nuclear antigen (PCNA), in primary chondrocytes as well as in tibia organ culture. In addition, CXCL12a increased the expression of Runx2, Col10 and MMP13 in primary chondrocytes and tibia organ culture system, implying a role of CXCL12a in chondrocyte maturation. Micromass cultures of limb-bud mesenchymal progenitor cells (MPCs) revealed that CXCL12a has a limited effect on early chondrogenesis, but significantly promoted maturation of chondrocytes. CXCL12a induced the phosphorylation of p38 and Erk1/2 MAP kinases and IκB. The increased expression of cyclin D1 by CXCL12a was significantly attenuated by inhibitors of MEK1 and NF-κB. On the other hand, p38 and Erk1/2 MAP kinase and NF-κB signaling were associated with CXCL12a-induced expression of Runx2 and MMP13, the marker of chondrocyte maturation. Conclusion: CXCL12a promoted the proliferation and maturation of chondrocytes, which strongly suggest that CXCL12a may have a negative effect on articular cartilage and contribute to OA progression.